Dynamics of Export Demand Determinants in Pakistan: Exploring Exchange Rate Volatility and Economic Context - Khalid, Mahmood (Journal of Business and Economic Options, 2022)
The significance of understanding the dynamics of export demand determinants in Pakistan cannot be overstated, particularly in the context of the country's economic development and global trade landscape. By delving into the intricacies of exchange rate volatility and its interaction with other factors influencing export demand, this study aims to offer valuable insights that can inform policy formulation and strategic decision-making. In exploring the dynamic effects of exchange rate volatility on export demand, it is essential to consider the broader economic context within which Pakistan operates. As a country heavily reliant on exports to drive economic growth and development, understanding the factors that shape export demand dynamics is paramount. Exchange rate volatility, for instance, can have profound implications for the competitiveness of Pakistani exports in international markets. Fluctuations in exchange rates can impact export prices, making Pakistani goods more or less attractive to foreign buyers. Moreover, the study also delves into the role of other conventional determinants of export demand, such as economic growth, trade policies, and external market conditions. By examining the interplay between these factors and exchange rate volatility, the research aims to provide a comprehensive understanding of the dynamics driving Pakistan's export performance. Furthermore, the use of OLS and ARDL models allows for a nuanced analysis of the relationship between export demand and its determinants across different time horizons. By capturing both short-term fluctuations and long-term trends, the study offers valuable insights into the underlying dynamics of Pakistan's export sector. Overall, the findings of this study are expected to have implications for policymakers, industry stakeholders, and researchers alike. By shedding light on the complex relationship between exchange rate volatility and export demand, the research contributes to a deeper understanding of the factors driving Pakistan's trade dynamics and can inform strategies aimed at enhancing export competitiveness and promoting sustainable economic growth.